Real-time insight into the multistage mechanism of nanoparticle exsolution from a perovskite host surface - Eleonora Calì; Melonie P. Thomas; Rama Vasudevan; Ji Wu; Oriol Gavalda-Diaz; Katharina Marquardt; Eduardo Saiz; Dragos Neagu; Raymond R. Unocic; Stephen C. Parker; Beth S. Guiton; David J. Payne (Nature Communications, 2023)
The separation of nanoparticles from oxide hosts by exsolution forms the basis for catalytic and energy-related applications. Here, the authors elucidate the multistep mechanism of exsolution at perovskite surfaces by combining real-time electron microscopy and computational methods.